Reasons behind Leaving Home at Old Age: A Case from Nepal - Ghimire, Mayanath; Shrestha, Eka Bahadur; Jayashree,; Thakur, Rashmi (GS WOW: Wisdom of Worthy Research Journal, 2024)
The study aims to investigate the reason why elderly individuals become detached from their families and choose to migration to elder homes in Nepal. A questionnaire was developed, and in-depth face-to-face interviews were conducted with elderly residents at Devghat Elder Home. A mixed-method approach (qualitative and quantitative) was employed to analyse the factors influencing elders to migrate in elders homes. Ethical considerations were observed, and consent was obtained from the elders. Data was collected through face-to-face interviews, including physical measurements. Analysis was conducted using SPSS and CDC tools. The study focused on three types of elder homes in Devghat, Chitwan: NRAN-constructed payable elder homes, Rotary Karunalaya Elder Home and Thaha Sadbarta. Region for migration included lack of space in their own homes, abuse form family members, and seeking peace and security. Elderly residents found solace in the peaceful environment, companionship, and respectful treatment at the elder home. The study revealed varying levels of nourishment among residents, with a prevalence of moderate thinness and instances of abuse and neglect leading to migration. Elderly individuals in Nepal face challenges such as abuse, neglect, and lack of familial support, promoting them to seek refuges in elder homes for a peaceful and secure living environment. Understanding the factors driving elderly migration to elder homes is crucial for addressing the needs of this vulnerable population.